IMPLEMENTATION OF INDEPENDENT LEARNING IN APPLIED PHYSICS COURSES - Stefany Margareta Martono; Vina N Van Harling (SOSCIED, 2022)
Freedom of learning is a curiculum set by the the government with the aim of giving Freedom to students to study according to their competence. Applied physics courses is one of the basic courses in the electrical engineering department. To make it easier for students to understand theory and practice, the researcher apply freedom of learning wuth the STEM. STEM is a learning method that combines several diciplines that produce solutions and products at the end of learning. The STEM method can hel students understand material, especially applied physics and aplly it so they can design and solve problems related to their knowledge in the electrical field. The researcher collected data, namely interview data conducted on several students who were randomly selected and represented in 1 project group as well as several students who took written exam. The result of the data analysis show that freedom to learn with STEM method in the Applied Physics course provides a basic understanding according to the field, especially the field of electrical engineering. Students are able to understand the basic measurements and electrical circuits.